2021
DOI: 10.1093/molbev/msab209
|View full text |Cite
|
Sign up to set email alerts
|

Genome Analysis Traces Regional Dispersal of Rice in Taiwan and Southeast Asia

Abstract: The dispersal of rice (Oryza sativa) following domestication influenced massive social and cultural changes across South, East, and Southeast Asia. The history of dispersal across islands of Southeast Asia, and the role of Taiwan and the Austronesian expansion in this process remain largely unresolved. Here, we reconstructed the routes of dispersal of O. sativa ssp. japonica rice through Taiwan and the northern Philippines using whole-genome re-sequencing of indigenous rice landraces coupled with archaeologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 72 publications
4
15
1
Order By: Relevance
“…100 km south of Taiwan and Lanyu [11,14] across the Bashi Channel (Fig 1). The conjecture that Yami represents a northward Austronesian migration from the Philippines to Taiwan is also consistent with the idea that Neolithic Taiwan was part of the integral maritime trade networks around the South China Sea [15][16][17]. Surprisingly, however, archaeological and genetic studies both suggest that Yami are closer to Formosan indigenous peoples than the Ivatan [18,19].…”
Section: Introductionsupporting
confidence: 74%
“…100 km south of Taiwan and Lanyu [11,14] across the Bashi Channel (Fig 1). The conjecture that Yami represents a northward Austronesian migration from the Philippines to Taiwan is also consistent with the idea that Neolithic Taiwan was part of the integral maritime trade networks around the South China Sea [15][16][17]. Surprisingly, however, archaeological and genetic studies both suggest that Yami are closer to Formosan indigenous peoples than the Ivatan [18,19].…”
Section: Introductionsupporting
confidence: 74%
“…Although various literature indicated that the Neolithic expansion was associated with the movements of domestic animals ( Diamond and Bellwood, 2003 ; Piper, 2017 ), a recent study suggest that this was unlikely for chickens as it favored the translocation route from MSEA via Sundaland, and subsequently followed by the southward diffusion from the Philippines into the Pacific islands ( Godinez et al, 2021 ). Moreover, contrary to the prediction of the out-of-Taiwan theory, there is recent evidence of gene flow of indigenous rice from Northern Luzon to Taiwan that occurred ∼1,300 years ago ( Alam et al, 2021 ) favoring the hypothesis of south to north expansion. Thus, this finding may stimulate scientific interest in the complexity of the introduction and dispersal of domestic pigs, particularly the Lanyu pig into the Philippines.…”
Section: Discussionmentioning
confidence: 81%
“…These patterns of genetic variation may also reflect the multifaceted history of rich trade and barter between travelers and coastal communities, including river movements in coastal settlements in the Philippines in prehistoric and protohistoric times ( Fox, 1967 ). For example, the extent of trade networks around the South China Sea and the Austronesian trade sphere, which included MSEA, Indonesia, the Philippines, Taiwan and southern China, and India to the west ( Hung et al, 2007 ; Alam et al, 2021 ) is very complex, which could likely be linked to the enormous movements of domestic animals and other material cultures. This could include domestic pigs, where episodic admixture of pig lineages from different geographic regions may have occurred, as indicated by the mtDNA signatures of present-day Philippine pig populations.…”
Section: Discussionmentioning
confidence: 99%
“…S3 , Supplementary Material online). Many of these expansions and population movements that occurred after ∼4 kya were likely triggered by the introduction of agriculture from Austronesian-speaking cultural communities ( Deng et al 2020 ; Alam et al 2021 ), perhaps coupled in some places with the growing influence of local Papuan agricultural practices that had commenced as early as ∼10 kya ( Denham and Haberle 2008 ).…”
Section: Resultsmentioning
confidence: 99%